2009
DOI: 10.1051/0004-6361/200912885
|View full text |Cite
|
Sign up to set email alerts
|

Orbital periods of cataclysmic variables identified by the SDSS

Abstract: We present time-resolved spectroscopy and photometry of SDSS J100658.40+233724.4, which we have discovered to be an eclipsing cataclysmic variable with an orbital period of 0.18591324 days (267.71507 min). The observed velocity amplitude of the secondary star is 276 ± 7 km s −1 , which an irradiation correction reduces to 258 ± 12 km s −1 . Doppler tomography of emission lines from the infrared calcium triplet supports this measurement. We have modelled the light curve using the lcurve code and Markov Chain Mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…D'Avanzo et al () observed Hα emission from the leading side of the inner face of the companion star in Cen X‐4 and attributed it to irradiation from the hotspot and shielding from the gas stream. Southworth et al () observed Hα emission from the secondary of J100658.40+233724.4. González Hernández & Casares () detected Hα emission from the secondary of the black hole system A0620−00 which they attributed to chromospheric activity induced by rapid rotation.…”
Section: Discussionmentioning
confidence: 99%
“…D'Avanzo et al () observed Hα emission from the leading side of the inner face of the companion star in Cen X‐4 and attributed it to irradiation from the hotspot and shielding from the gas stream. Southworth et al () observed Hα emission from the secondary of J100658.40+233724.4. González Hernández & Casares () detected Hα emission from the secondary of the black hole system A0620−00 which they attributed to chromospheric activity induced by rapid rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Mukadam et al (2011) used this information to discovered the only known outburst of CV SDSS J074531.92+453829.6. Similarly, Southworth et al (2009) used the data to find and constrain the rate of outbursts for eclipsing CV SDSSJ100658.40+233724.4.…”
Section: Photometric Follow-upmentioning
confidence: 99%
“…In this section we provide a concise description of the code, LCURVE, that we wrote in order to model the light-curves of this paper; the same code has been used in Pyrzas et al (2009) and Southworth et al (2009). The aim of the code was to provide a flexible framework for fitting light-curves characteristic of eclipsing dwarf novae and detached white dwarf / M dwarf binary stars.…”
Section: Discussionmentioning
confidence: 99%